Clinical Significance of the Resistance Proteins LRP, Pgp, MRP1, MRP3, and MRP5 in Epithelial Ovarian Cancer. Issue 2 (1st February 2015) - Sedláková, Iva; Laco, Jan; Caltová, Katerina; Cervinka, Miroslav; Tošner, Jindrich; Rezác, Adam; Špacek, Jirí
Abstract : Objective: This study aimed to evaluate the correlation between the expressions of lung resistance protein (LRP), P-glycoprotein (Pgp), multidrug resistance-associated protein (MRP)-1, MRP3, and MRP5 and histopathological parameters and clinical outcome, and to determine the predictive and prognostic value of these transport proteins in patients with ovarian cancer. Methods: Tumor samples from 111 chemonaive patients with epithelial ovarian cancer who underwent primary surgery from 2006 to 2010 were immunohistochemically stained for LRP, Pgp, MRP1, MRP3, and MRP5 expressions. Results: MRP1 expression was greater among patients with late disease than among patients with early stage ovarian cancer [International Federation of Gynecology and Obstetrics (FIGO) I + II, 71.6% (confidence interval, 60–100); FIGO III + IV, 83.6% (confidence interval, 100–100); P = 0.03]. The histological subtype correlated with the expressions of LRP, Pgp, MRP1, and MRP3. Relapse of disease during the next 24 months occurred more often among patients with higher Pgp and MRP1 than among patients with lower Pgp and MRP1 expressions. FIGO stage, histological type, debulking efficiency, strong Pgp expression, and strong MRP1 expression correlated significantly with shorter progression-free survival (log-rank test, P = 0.001, P = 0.004, P = 0.001, P = 0.051, and P = 0.046, respectively). FIGO stage, histological type, debulking efficiency, and strong MRP1 expression correlated with poor patient survival (log-rank test, P = 0.001, P = 0.042, P = 0.005, and P = 0.018, respectively). Conclusions: Pgp and MRP1 expressions were clinically significant in patients with ovarian cancer. Pgp and MRP1 may be reliable, independent predictive and prognostic factors regarding the clinical outcome of ovarian cancer. MRP3 is less important as a predictive and prognostic factor than MRP1 expression. MRP5 and LRP expressions were not applicable prognostic parameters regarding ovarian cancer.